Initiation and completion rates for latent tuberculosis infection treatment: a systematic review. Issue 1 (December 2016) - Sandgren, Andreas; Vonk Noordegraaf-Schouten, Marije; van Kessel, Femke; Stuurman, Anke; Oordt-Speets, Anouk; van der Werf, Marieke
Abstract Background Control of latent tuberculosis infection (LTBI) is an important step towards tuberculosis elimination. Preventive treatment will prevent the development of disease in most cases diagnosed with LTBI. However, low initiation and completion rates affect the effectiveness of preventive treatment. The objective was to systematically review data on initiation rates and completion rates for LTBI treatment regimens in the general population and specific populations with LTBI. Methods A systematic review of the literature (PubMed, Embase) published up to February 2014 was performed. Results Forty-five studies on initiation rates and 83 studies on completion rates of LTBI treatment were found. These studies provided initiation rates (IR) and completion rates (CR) in people with LTBI among the general population (IR 26–99 %, CR 39–96 %), case contacts (IR 40–95 %, CR 48–82 %), healthcare workers (IR 47–98 %, CR 17–79 %), the homeless (IR 34–90 %, CR 23–71 %), people who inject drugs (IR 52–91 %, CR 38–89 %), HIV-infected individuals (IR 67–92 %, CR 55–95 %), inmates (IR 7–90 %, CR 4–100 %), immigrants (IR 23–97 %, CR 7–86 %), and patients with comorbidities (IR 82–93 %, CR 75–92 %). Generally, completion rates were higher for short than for long LTBI treatment regimens. Conclusion Initiation and completion rates for LTBI treatment regimens were frequently suboptimal and varied greatly within and across different populations.